Estrategias Lúdicas para fomentar las tradiciones culturales en estudiantes de Básica Media de la Unidad Educativa “República de Francia” - Briceño Martínez, Marisol de los Ángeles (2022)
This research has been developed as a response to the need to provide quality teaching and the use of an appropriate methodology that highlights the relevance of cultural traditions and their benefits for constructing cultural identity through playful strategies. Besides, this research aims at determining the incidence of lively strategies promoting cultural practices in students from middle school of the institution "República de Francia" of Zamora Chinchipe province. Moreover, there are three specific objectives: Identify the current state of cultural traditions, establish the factors that affect students in secondary school, and develop a guide with playful strategies that allow teachers to promote cultural practices in their students. For this purpose, the present research was developed under the mixed-method approach through a systematic process. The type of qualitative-descriptive research methods, such as scientific, deductive, and analytical, were also considered. The use of interview and survey techniques were the primary data collection instruments applied to the teacher and students. The results indicated that there is a lack of knowledge among the students regarding the cultural traditions of their region and country. Furthermore, there is a poor initiative in applying playful strategies to issues of interculturality. Lastly, it was found that the teacher does not use active methods to promote learning based on education and cultural tradition to get students to value and recognize their traditions. KEYWORDS: Strategies, games, learning, traditions, culture.